Los estudios de Biblioteconomía y Documentación en el Reino Unido. Un caso específico: la universidad de Sheffield - Muñoz de Solano y Palacios, Bárbara (Revista General de Información y Documentación, 2003)
The larger kingdoms of medieval Europe —Italy, France, England— established their first universities as early as the 12th century. The University of Sheffield was founded in 1905 and the Department of Information Studies in 1963 as the Postgraduate School of Librarianship. Nowadays, Its offers a wide range of degree programs from undergraduate level through to postgraduate taught masters. This article focuses on the subject content covered in the modules related to the Information Science.